Antioxidant activity of mangifera indica of chok anan and lemak manis peel extract - Mohamad Aizat, Padir (2015)
Mangoes (Mangifera indica) are one of the most important tropical fruits as it contributes to global production exceeding 26 million tons in 2004. In Malaysia, it shares 4.5 % in global imports of mangoes which make Malaysia up to top ten among other mangoes producing countries. Almost 33-85% of the fresh fruit are edible pulp, while the kernel and the peel amount to 9-40% and 7-24% respectively. However, the by-products of industrial mango processing are about 35-60%, of the total fruit weight. There are a lot of researches to sustain the agricultural production because these by-products .cause serious disposal problem. The usage of the mango kernels source of fat, antioxidants, starch, flour and feed, has, already been studied but studies on peels are scarce. Synthetic antioxidants posed critical health concern because it has proven to be carcinogenic. Hence developing antioxidant from agro-based by-product would be good alternative. Antioxidant is able to delay the oxidation of a substrate by inhibiting the initiation of oxidising chain reaction caused by free radicals. Antioxidant can prevent fats and oils from becoming rancid and protects body from damaging effects of free radicals. Mangoes of different cultivars were evaluated for antioxidant potential by biochemical assay which is DPPH and tested for their phenolic contents. The highest phenolic content was found in M. indica Chok Anan than M. indica Lemak Manis. When the total phenolic content is high, the percentage of antioxidant activity also high. Chok Anan shows the lowest IC₅ₒ when compared with Lemak Manis with 0.368 and 0.474 respectively. M. indica Chok Anan shows highest total phenolic content in each solvent than M. indica Lemak Manis. This shows the percentage of antioxidant is highest in M. indica Chok Anan. While methanol shows the most effective solvent on extracting the phenolic compounds on M. indica.